The Importance of Educational Institutions for the Employees'Professional Development - Mirela Minică; Lavinia-Maria Nițulescu; Alina Constantin (Babes-Bolyai University, 2023)
The continuous professional training of didactic personnel at the level of the pre-university education system is coordinated at the level of the Ministry of Education, in accordance with national strategies and policies. This includes professional development and career development according to art. 242, para. (1) the National Education Law no. 1/1011, with subsequent amendments and additions. Continuous training is both a RIGHT and an OBLIGATION, according to the legislation in force (https://www.edu.ro/formare-continua). Involving the school in providing professional development opportunities for teachers helps them develop their skills, improve their teaching practices and feel supported in their professional development. A collaborative school culture, based on mutual support, between teachers and between teachers and the school principal positively influences the teachers' motivation, teaching quality and job satisfaction (Eurydice, 2015). The present paper presents the results of a quantitative study (a sociological survey based on a questionnaire), with the aim of identifying the perception of didactic personnel regarding the contribution of the educational institution to their career development. It starts from the following premise: the more the educational institution gets involved in the professional training activities of its didactic personnel, the more teachers will be motivated for career development.